Temperature inversion in a gravitationally bound plasma: Case of the solar corona - Barbieri, Luca; Casetti, Lapo; Verdini, Andrea; Landi, Simone (arXiv.org, 2023)
The temperature of the solar atmosphere increases from thousands to millions of degrees moving from the lower layer (chromosphere) to the outermost one (corona), while the density drops accordingly. The mechanism behind this phenomenon, known as a temperature inversion, is still unknown. In this work, we model a coronal loop as a collisionless plasma confined in a semicircular tube that is subject to the Sun's gravity and in thermal contact with a fully collisional chromosphere behaving as a thermostat at the loop's feet. By using kinetic \(N\)-particle simulations and analytical calculations, we show that rapid, intermittent, and short-lived heating events in the chromosphere drive the coronal plasma towards a non-equilibrium stationary state. The latter is characterized by suprathermal tails in the particles' velocity distribution functions, exhibiting temperature and density profiles strikingly similar to those observed in the atmosphere of the Sun. These results suggest that a million-Kelvin solar corona can be produced without the local deposition of heat in the upper layer of the atmosphere that is typically assumed by standard approaches. We find that suprathermal distribution functions in the corona are self-consistently produced instead of postulated a priori, in contrast to classical kinetic models based on a velocity filtration mechanism.